2017
DOI: 10.1111/ene.13385
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography imaging in gliomas: applications in clinical diagnosis, for assessment of prognosis and of treatment effects, and for detection of recurrences

Abstract: Neuroimaging plays a significant role in the diagnosis of intracranial tumours, especially brain gliomas, and must consist of an assessment of location and extent of the tumour and of its biological activity. Therefore, morphological imaging modalities and functional, metabolic or molecular imaging modalities should be combined for primary diagnosis and for following the course and evaluating therapeutic effects. Magnetic resonance imaging (MRI) is the gold standard for providing detailed morphological informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 167 publications
(222 reference statements)
0
8
0
Order By: Relevance
“…Also, MRS is restricted in borderline areas and is not available for the entire brain. 11 ASL and DTI are hindered by relatively lower spatial resolutions and longer scanning protocols. To note, T1WI and T2 FLAIR sequences are robust and have gained widespread clinical acceptance in neuroradiology practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, MRS is restricted in borderline areas and is not available for the entire brain. 11 ASL and DTI are hindered by relatively lower spatial resolutions and longer scanning protocols. To note, T1WI and T2 FLAIR sequences are robust and have gained widespread clinical acceptance in neuroradiology practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been generally reported that advanced MRI sequences are more accurate than conventional ones, 9 certain limitations hinder the popularity of advanced functional MRI sequences. 10,11 In comparison with other functional MR imaging methods, classic T1WI and T2 FLAIR sequences are less vulnerable to artifacts, more accessible, and allow for higher spatial resolution. 9 However, other tissue sources of bright signal appear as high signal on precontrast T1WI or T2 FLAIR, which greatly influence traditional enhancement observation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, fluorodeoxyglucose positron emission tomography (FDG-PET) has emerged as a pivotal imaging modality in clinical oncology [1][2][3][4][5][6][7]. Currently, thousands of PET scanners have been installed worldwide and are extensively used for diagnosis and staging of malignant tumors [8][9][10][11][12] and assessment of response to radiochemotherapy [13][14][15][16]. It is reported that PET results alter staging and treatment management in nearly 40% of patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, which is an update of a previously published paper [13], clinically relevant results studying glucose metabolism, amino acid uptake, and cell proliferation with PET tracers are summarized. Other tracers specifically applied for research topics [4,14] are not discussed.…”
Section: Introductionmentioning
confidence: 99%